Ethno mathematics-based teaching materials for elementary school students - Edy Purwanto; Rochmiyati Rochmiyati; Nurhanurawati Nurhanurawati (International Journal of Educational Studies in Social Sciences (IJESSS), 2021)
This study aims to develop teaching materials based on ethno mathematics. A Research and Development (R&D) method as used in this research. Meanwhile, the research design of teaching materials developed using ADDIE included five stages, namely analyze, design, development, implementation, and evaluation. The feasibility of this ethno mathematical-based teaching material refers to the results of the assessments of three experts, namely education expert, ethno mathematics expert, and mathematicians, as well as students’ responses. The students' responses used as a trial were made by fifth-grade students of SDN Negara Bumi, Central Sungkai Subdistrict. The results of this study indicate that the teaching materials developed based on ethno mathematics have met the standards of feasibility aspects which include validity, practicality, and effectiveness of teaching materials.